IMPLEMENTATION OF MICROCOMPUTER BASED LABORATORY IN PHYSICS CLASS: STUDENTS' PERCEPTIONS - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2012)
Using of well integrated instructional technologies such as Microcomputer Based Laboratories (MBL) enables students to gather, analyze and interpret data. The purpose of this study was to investigate the effectiveness of MBL technology on students' learning by taking students' perceptions into account. A multi-case study design guided the research. The participants of the study were nine ninth-grade students. This research lasted five weeks for the period of teaching Optics concepts such as illumination, brightness, light, and polarization. The data were collected by semi-structured interviews, which were video-recorded. Assertions were drawn from the data. Students realize that MBL technology enables learning with discovery and promotes durability of knowledge. Students are pleased that MBL gives opportunities for understanding graphs, collecting quantitative data through sensors, retesting previous predictions in a short time and understanding variables as well as relationships between them. Moreover, students think that MBL is exciting and supports a learning environment where they have fun. It can be concluded that students' overall perception about MBL usage in physics class is positive. This current study contributes to the literature by adding students' perception about how MBL technology facilitates their learning.
Keywords: Microcomputer Based Laboratory; optics; technology; perceptions; REPRESENTATIONS